Screen Space Global Illumination Using Radiance Cascades in 3D Video Games - Abou Dan, Ghaith; Jensen, Mati (My University, 2025)
Achieving accurate Global Illumination (GI) is essential for creating visually compelling and photorealistic imagery in computer graphics. Recent advancements in GI typically require temporal accumulation or reuse of samples in order to achieve real-time performance at a good quality. However, interactive video games may require GI solutions that respond quickly to user interaction and rapidly changing lighting conditions. We develop a lighting method for video games, specifically designed for the constraints present in the game As We Descend by Box Dragon, where the camera has limited movement and all relevant parts of the scene are on screen at all times, contains many short lasting emissive visual effects, with a budget of a few milliseconds per frame on modern hardware. To create a method for these conditions, we make use of ideas first presented by Alexander Sannikov for use in Path of Exile 2, Radiance Cascades (RC), which is an efficient data structure for representing a lightfield [Ale23]. We make use of a recent screen-space lighting technique, Visibility Bitmask Global Illumination (VBGI) [TLG23] combined with RC, by placing probes in screen-space. We detail many of the optimizations and adjustments needed to combine these techniques, and allowing them to run in real-time. During evaluation, we go over various parameters that allow scaling the method to various performance levels, allowing it to run at down to 2ms at the lowest settings, 6 milliseconds at medium settings, and 26 milliseconds on high settings, with a memory usage ranging from 0.03GiB to 3.9GiB depending on the settings. At this performance, it can achieve one bounce screen-space global illumination along with emissive lighting, with a radius that covers the entire screen. The method has no high-frequency noise without the use of a separate denoising pass, and does not use temporal accumulation or reuse which would otherwise lead to temporal artifacts. The method is not without issue, as there are many limitations and artifacts, and is an approximation of ground truth GI. Firstly, anything that is off-screen cannot contribute or occlude lighting, the chosen screen-space tracing method causes over-brightening of the background, and upscaling radiance data causes artifacts at especially lower settings. Worst is that the method is prone to flickering during even small movements, especially at lower settings, significantly worsening any artifacts present as artifacts become flickery.
Keywords: 3D Graphics; Rendering; Real-Time Rendering; Global Illumination; Radiance Cascades; Visibility Bitmask Global Illumination; Lighting; Screen-Space Lighting; Screen-Space Global Illumination